Sociodemographic Differences in Prenatal Diagnosis of Chromosomal Anomalies: A Population-Based Study - Santoro, Michele; Mezzasalma, Lorena; Coi, Alessio; Baldacci, Silvia; Pasquini, Lucia; Pierini, Anna (Frontiers in Pediatrics, 2021)
Background. In Europe, about 76% of cases of chromosomal anomalies are prenatally diagnosed. Prenatal diagnosis allows more efficient planning of postnatal treatment and helps parents for an informed decision about the continuation of pregnancy. The main aim of this study was to evaluate whether the sociodemographic maternal characteristics affect the access to prenatal diagnosis of chromosomal anomalies. Methods. Cases of chromosomal anomalies in the period 2005-2017 came from the population-based registry of congenital anomalies of Tuscany (Italy). Differences in the access to prenatal diagnosis were investigated through the following maternal characteristics: education, geographic origin and occupation. The association between cases of termination of pregnancy after prenatal diagnosis and maternal characteristics was also analysed. Odds Ratios (OR) adjusted by maternal age were calculated using logistic regression models. Results were provided for all cases of chromosomal anomalies and for Down syndrome cases. Results. A total of 1,419 cases were included in the study. Cases prenatally diagnosed were 1,186 (83.6%). We observed a higher proportion of cases not prenatally diagnosed among cases with low maternal education compared to those with high maternal education (OR=2.16, p<0.001) and in women from high migratory outflow countries, compared to the Italian ones (OR=2.85, p<0.001). For prenatally diagnosed Down syndrome cases, we observed a higher proportion of termination of pregnancy for women with low education level (OR=4.36, p=0.023). Conclusions. In our study evidence of differences in the access to prenatal diagnosis of chromosomal anomalies associated with maternal education and geographic origin was found. Population-based studies investigating sociodemographic disparities can provide essential information for targeted public health programs. Further studies are recommended to monitor the impact of the increasing availability of non-invasive screening tests.